Kesantunan Tuturan Imperatif dalam Film Habibie dan Ainun 3 Sutradara Hanung Bramantyo - Fadhilah Hidayati; Ermawati S (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
Abstrac This research is entitled "Imperative Speech Politeness in the Film Habibie and Ainun 3, Directed by Hanung Bramantyo". The problems contained in this study are: (1) How is the imperative speech in the film Habibie and Ainun 3 directed by Hanung Bramantyo? (2) What is the scale of imperative speech politeness in the film Habibie and Ainun 3, directed by Hanung Bramantyo?. The purpose of this study (1) to identify, describe and conclude imperative speech in the film Habibie and Ainun 3, directed by Hanung Bramantyo. (2) Identify, describe and conclude the scale of imperative speech politeness in the film Habibie and Ainun 3, directed by Hanung Bramantyo. This study uses a qualitative approach and the research method used is descriptive. The theory used in this study is the theory of Leech (1983) in Rahardi (2005). The data in this study is the speech of the characters in the film Habibie and Ainun 3, directed by Hanung Bramantyo, which contains imperative speech. Based on the research conducted, it can be concluded that (1) The most frequently used imperative utterances in the film are ordinary imperative utterances, which were found to be 44 utterances. (2) The most frequently used imperative speech politeness scale in the film is the social distance scale, which found 33 utterances.